Evaluasi dan Penguatan Organizational Resilience di Perguruan Tinggi Vokasi: Pendekatan Systematic Literature Review (SLR) dalam Menjawab Tantangan Institusional: Penelitian - Nika Sintesa Grinika; Rais Hidayat (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to explore and identify factors that strengthen organizational resilience in vocational colleges using the Systematic Literature Review (SLR) approach method based on the PRISMA model. This study was conducted on 25 scientific articles indexed by Scopus for the 2020-2025 period and selected based on relevant topic criteria. Data was collected from Harzing's Publish or Perish (PoP) application taken from Crossref and Google Scholar. The identification process uses keywords such as